Ghana: Agricultural Information Network System (GAINS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Agricultural Information Network System (GAINS) was established in 1991 as a component of the National Agricultural Research Project (NARP).